Slowly Evolving Trends in Temporal Lobe Epilepsy Management at London Health Sciences Centre - Blume, Warren T. (Hindawi Publishing Corporation, 2013)
Although the advent of MRI impacted significantly our presurgical investigation, ictal semiology with interictal and ictal EEG has clearly retained its roles in localizing epileptogenesis. MRI-identified lesions considered epileptogenic on semiological and electroencephalographic grounds have increased the likelihood of resective surgery effectiveness whereas a nonlesional MRI would diminish this probability. Ictal propagation and the interplay between its source and destination have emerged as a significant component of seizure evaluation over the past 30 years.